Coexisting squamous cell carcinoma and high-grade neuroendocrine carcinoma, small cell type: a rare collision in cervix. (18th May 2018) - Kaushal, Seema; Mathur, Sandeep R; Kumar, Sunesh
Abstract : Collision tumours of the uterine cervix are extremely uncommon with exact incidence not known. Unlike squamous cell carcinoma (SCC) and adenocarcinoma that are known to coexist, small cell neuroendocrine carcinoma (SCNEC) is rarely documented with other histological types in the cervix. We report such rare case of a collision tumour in cervix displaying dual histological component of SCNEC and SCC in a 36-year-old woman. The case is being presented because of its rarity and represents a unique and hitherto seldom-reported combination of two malignant tumours with distinct and often contrasting epidemiology, histology and prognosis coexisting in the same patient.